Pengaruh Perbandingan Tepung Kacang Tunggak (Vigna unguiculata (L.) Walp) Dengan Buah Anggur Bali (Vitis vinifera) Kering Terhadap Karakteristik Snack Bar - Sela Gracia Ginting, Almadea; Yusa, Ni Made; Timur Ina, Putu (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 11 No 2 (2022): Jurnal ITEPADO - 10.24843/itepa.2022.v11.i02.p06, 2022)
The purpose of this study was to determine the effect of cowpea flour and dried grape to the characteristics of snack bar and the right ratio of cowpea flour and dried grape that was able to produce snack bar with the best characteristics. The Completely Randomized Design was used in the research with treatment ratio of cowpea flour and dried grape which consisted of 5 levels: 90%:10%; 80%:20%; 70%:30%; 60%:40%; and 50%:50%. The treatment was repeated 3 times to obtain 15 units of experiment. The data obtained were analyzed by variance and if the treatment had an effect on the observed variable then continued with Duncan’s Multiple Range Test. The result showed that cowpea flour and dried grape had a significant effect on water content, ash content, fat content, protein content, carbohydrate content, crude fiber content, total energy, antioxidant activity, color (hedonic), texture (hedonic and scoring), aroma (hedonic), taste (hedonic), and overall acceptance (hedonic). Comparison of 50% cowpea flour : 50% dried grape produced snack bar with the best characteristics, specifically: water content 10.18%, ash content 2.22%, fat content 17.83%, protein content 8.83%, carbohydrate content 60.94%, crude fiber content 8.95%, total energy 439.56 kcal, antioxidant activity 53.62%, color liked, texture tender and liked, aroma liked, taste liked and overall acceptance liked.